Constructing the Postmodernist Identity: the Case of Michael Ondaatje's The English Patient - Stankevičiūtė, Kristina (Respectus Philologicus, 2003)
The article discusses the problem of identity in the novel of the Canadian writer Michael Ondaatje, The English Patient. The characters of the novel are created with the help of postmodernist techniques and concepts: narrative discontinuity, mini-narratives, fragmented story-line, decentered and dehumanized subject, chaotic time and space organization, the absence of a single truth and rejection of a single, objective evaluation of history, war, love, betrayal. Analysing the personality of the main character - the mysterious English patient - the article tries to disclose how the novel, using the postmodernist tools, questions and constructs the notions of identity and the subject's self.
Keywords: fragmentic; identity; narrative discontinuity; mini-narrative; postmodern; self; subject; text